2000
DOI: 10.1111/j.1528-1157.2000.tb04603.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Synthase Expression in the Cerebral Cortex of Patients with Epilepsy

Abstract: The fact that NOS upregulation is more evident in patients with a long seizure history suggests that this is a consequence of seizures, acting probably as an adaptative response to the sustained release of excitatory amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 77 publications
(88 reference statements)
4
17
0
2
Order By: Relevance
“…Our results indicate that variations in nNOS (but not in eNOS) expression could be a main factor in the changes in NOS activity changes appearing after epileptic seizures, which agrees with the above mentioned studies in patients and cell culture (González-Hernández et al, 2000;Catania et al, 2003;Kamida et al, 2007;González-Martínez et al, 2009). No differences were found between the non-stimulated GASH:Sal and control hamsters, suggesting that in our model nNOS may be more involved in the response to the epileptic seizures than in the susceptibility to suffer a crisis.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results indicate that variations in nNOS (but not in eNOS) expression could be a main factor in the changes in NOS activity changes appearing after epileptic seizures, which agrees with the above mentioned studies in patients and cell culture (González-Hernández et al, 2000;Catania et al, 2003;Kamida et al, 2007;González-Martínez et al, 2009). No differences were found between the non-stimulated GASH:Sal and control hamsters, suggesting that in our model nNOS may be more involved in the response to the epileptic seizures than in the susceptibility to suffer a crisis.…”
Section: Discussionsupporting
confidence: 93%
“…No differences were found between the non-stimulated GASH:Sal and control hamsters, suggesting that in our model nNOS may be more involved in the response to the epileptic seizures than in the susceptibility to suffer a crisis. This notion agrees with previous experimental studies indicating that NOS was produced as a consequence of convulsant administration (Masukawa et al, 1998;Kaneko et al, 2002) and also supports results of clinical studies where a higher increase in nNOS production was found in surgical patients with a prolonged history of seizures (González-Hernández et al, 2000).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…NO is involved in the pathophysiology of epilepsy, and the expression of nNOS in neurons is increased in epileptic patients and pilocarpine-induced animal models of epilepsy [62] . Systemic treatment with a highly selective nNOS inhibitor, L-NPA, reduces the severity and duration of seizures, the EEG power in the gamma band, and the frequency of epileptiform spikes during SE, suggesting that nNOS facilitates seizure generation and may be with the development of chronic epilepsy, especially in the early stages [63] .…”
Section: Nitri C Oxide Synthase and Epilepsymentioning
confidence: 99%